Effect of Sri Lankan Traditional Medicine and Ayurveda Management on Endometriosis and Adenomyosis: A Case Study - Karunagoda, K.P.K.R.; Deepthika,S.H.K. (University of Colombo, Sri Lanka, 2024)
Endometriosis affects about 10% of reproductive-age women and girls worldwide. Adenomyosis is a form of the endometriosis where endometrial glands found deep within the myometrium. This study is aimed to showcase a successful management approach for a case involving both endometriosis and adenomyosis. This case study invovles of a patient diagnosed with both endometriosis and adenomyosis with multiple endometrioma in right and left ovaries. She is a 42-year married nulliparous woman without other pathologies. Her body mass index (BMI) is 26.8, blood pressure is 120/78 mmHg, and pulse rate is 78/min. She has a history of laparoscopic bilateral cystectomy in 2021. The intervention period lasted three months. The first drug regimen was administered during OPD management, followed by two IPD treatment regimens 01 month apart. Sneha sweda, Yoga vasti, Nadi sweda, Udara pattu, Mathra vasti procedures were conducted with the 2nd and 4th oral drug regimen. In between 3rd drug regimen was continued at OPD level. Dysmenorrhea and dyspareunia were assessed monthly using Visual Analog Scale (VAS). Endometriomas and adenomyosis were evaluated before and after the intervention by ultrasound scans conducted by the experts who were blinded to the procedure. Other vital signs and menstrual patterns were monitored every 2 weeks. After the treatments, the VAS score for dysmenorrhea reduced to 10 from 0, and the VAS score for dyspareunia reduced from 4 to 1. The ultrasound scan reports confirmed the total cure of the endometrioma and adenomyosis after the three-month intervention. During the follow up period, the patient’s quality of life (QOL) remained unchanged. In conclusion this case was successfully managed using Sri Lankan traditional and Ayurveda treatments.
Keywords: Endometriosis; Adenomyosis; Sri Lankan Traditional Medicine; Ayurveda; Case Study